Trend of homicide rates in Santa Catarina by micro-regions: 1996 to 2019 - Bando, Daniel (2022)
Context: Homicide is a public health and security problem. The objective of this work was to evaluate trends in homicide rates by micro-regions in the state of Santa Catarina. Methods: This is an ecological time series study. Data were collected by the Informatics Department of the Unified Health System and by the National Census. The segmented linear regression technique was used to estimate annual percentage changes (APC) with a 95% confidence interval and possible inflection points by the joinpoint software. Results: in the period studied, there were 16,408 homicides in Santa Catarina, corresponding to a rate of 11.3 cases per 100,000 inhabitants. From 2003 to 2017, there was a trend towards an increase in homicide with a APC of +1.28. The following areas showed an upward trend in more than half of the study period: Araranguá, Blumenau, Chapecó, Criciúma, Itajaí - Ituporanga - Tijucas, Tabuleiro. In contrast, the micro-regions of Florianópolis, Curitibanos, Canoinhas showed a decreasing trend; the others remained stable. Conclusions: 38.9% of the study areas showed an upward trend in homicide rates, 16.7% showed a downward trend and 44.4% remained stable.